Analytical solution for the time dependent self-diffusion coefficient of a liquid in a porous medium - Loskutov, Valentin; Sevriugin, Vyacheslav (Diffusion Fundamentals, 2007)
The purpose of our work is to attempt to find the analytical expression approximating the experimentally obtained D(t) dependence of molecules of liquids or gases, in porous systems. The statement of the problem is based on the most general representations of self-diffusion processes in porous systems.